2017
DOI: 10.1093/cercor/bhx095
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activity, TGFβ-Signaling and Unpredictable Chronic Stress Modulate Transcription of Gadd45 Family Members and DNA Methylation in the Hippocampus

Abstract: Neuronal activity is altered in several neurological and psychiatric diseases. Upon depolarization not only neurotransmitters are released but also cytokines and other activators of signaling cascades. Unraveling their complex implication in transcriptional control in receiving cells will contribute to understand specific central nervous system (CNS) pathologies and will be of therapeutically interest. In this study we depolarized mature hippocampal neurons in vitro using KCl and revealed increased release not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 85 publications
2
48
0
Order By: Relevance
“…Studies in humans found an association between certain FOXN3 polymorphisms and suicidal attempts (Galfalvy et al., ; Sokolowski, Wasserman, & Wasserman, ) and increased FOXN3 levels in the PFC of suicide victims (Le‐Niculescu et al., ; Zhurov et al., ). A recent study in a mouse model of depression found decreased Foxn3 expression in the adult hippocampus (Grassi et al., ). Foxn3 expression is activity dependent and undergoes demethylation, resulting in increased expression (Grassi et al., ), suggesting paroxetine‐induced changes in dendritic spine formation and mitochondrial trafficking to the dendrites may be upstream of changes in Foxn3 expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies in humans found an association between certain FOXN3 polymorphisms and suicidal attempts (Galfalvy et al., ; Sokolowski, Wasserman, & Wasserman, ) and increased FOXN3 levels in the PFC of suicide victims (Le‐Niculescu et al., ; Zhurov et al., ). A recent study in a mouse model of depression found decreased Foxn3 expression in the adult hippocampus (Grassi et al., ). Foxn3 expression is activity dependent and undergoes demethylation, resulting in increased expression (Grassi et al., ), suggesting paroxetine‐induced changes in dendritic spine formation and mitochondrial trafficking to the dendrites may be upstream of changes in Foxn3 expression.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study in a mouse model of depression found decreased Foxn3 expression in the adult hippocampus (Grassi et al., ). Foxn3 expression is activity dependent and undergoes demethylation, resulting in increased expression (Grassi et al., ), suggesting paroxetine‐induced changes in dendritic spine formation and mitochondrial trafficking to the dendrites may be upstream of changes in Foxn3 expression.…”
Section: Discussionmentioning
confidence: 98%
“…Together with BDNF, TGFB may regulate DNA methylation in the hippocampus [35]. SB-431542 is a small-molecular inhibitor of TGFBR1 developed by GSK; it has been investigated for antitumor activities, though the effects of this molecule on mood and behavior will need to be explored in preclinical models [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, reduced occupancy of GADD45B on the Bdnf IX promoter was found, which is in line with reduced Bdnf IX expression (Gavin et al, 2012 ). Recently, GADD45B expression was shown to be regulated by transforming growth factor beta (TGFB) signaling and protein levels of GADD45B are reduced in a model of chronic mild stress (Grassi et al, 2017 ). Moreover, a reduction in expression levels of the immediate early gene Arc was also associated with reduced levels of GADD45B and DNA demethylation in this stress model (Grassi et al, 2017 ).…”
Section: Role Of Dna Demethylation In Neurological Disordersmentioning
confidence: 99%